THE ROLE OF ENGLISH LANGUAGE TEACHING IN DEVELOPING CRITICAL THINKING SKILLS AMONG UNIVERSITY STUDENTS - Tokumbetova Mekhribonu Shavkat qizi (Western European Studies, 2025)
This article explores the critical role of English Language Teaching (ELT) in fostering critical thinking skills among university students. As English continues to serve as the global language of academia and professional communication, its pedagogical function has evolved beyond linguistic competence toward cultivating intellectual autonomy, analytical reasoning, and reflective judgment. Drawing from educational psychology and applied linguistics, this paper argues that English language classrooms can serve as effective platforms for critical inquiry when instruction emphasizes problem-solving, interpretation, evaluation, and creativity. The study concludes that integrating critical thinking frameworks within ELT contributes to developing globally minded, independent learners capable of engaging with complex academic and societal issues.
Keywords: Critical thinking; English language teaching; higher education